Formulation and Antioxidant Activity Test of Micellar Water Extracted from Mangosteen Fruit Peel (Garcinia mangostana L.) Using the DPPH Method with Variations in the Concentration of PEG-7 Glyceryl Cocoate as a Surfactant - Andriyani, Yunita; Fadel, Muhammad Nurul; Besan, Emma Jayanti (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to determine the effect of PEG-7 glyceryl cocoate at concentrations of F1 0.2%, F2 0.4%, and F3 0.6% on the physical stability and cleaning power of micellar water preparations containing mangosteen peel extract. The best formulation was then tested for its antioxidant activity using the DPPH method. Research Method: This study used a laboratory experimental method. The variations in PEG-7 glyceryl cocoate concentration used in the micellar water extract of mangosteen peel were F1 (0.2%), F2 (0.4%), F3 (0.6%), and negative control F0 (0%). Evaluations were conducted on physical stability tests (organoleptic, pH, homogeneity, and viscosity) and cleaning power. The best micellar water formulation was then tested for antioxidant activity using the DPPH method. The test results were analyzed using a One-Way ANOVA test. Results and Discussion: The results of testing F3 micellar water, with the highest concentration of PEG-7 glyceryl cocoate, demonstrated that it was the best formula and exhibited the best cleaning ability. The results of the analysis using one-way ANOVA showed a p-value of < 0.05. The antioxidant activity of F3 was determined to have an IC50 of 103.81 μg/ml, which falls within the moderate category. Implications: The results of this study indicate that PEG-7 glyceryl cocoate at a concentration of 0.6% can be used as a surfactant in micellar water preparations of mangosteen peel extract. Further research is needed to determine the long-term stability of the preparation.